Looking into Cultural Diversity through 90 Day Fiancé: Intercultural Couple Analysis of Nicole and Azan’s Scenes - Utami, Shantika Budhi; Adi, Ida Rochani (Rubikon : Journal of Transnational American Studies, 2024)
This article analyzes comfort and enjoyment between networks and viewers is seen in reality show's popularity. This study conducting skeptical post-modern by Rosenau (1991) as for the approach. The study-case approach focuses on the planning and execution of research. It appears that the cultural diversity that is being portrayed on the reality TV program 90 Day Fiancé through Nicole and Azan’s scenes is intended to be a well-liked sub-genre of alternative fiction. As a result, the scenes and everything else in the show might all have been made up to suit the preferences of the viewers. Thus, there are two opposing viewpoints among viewers in this case: first, those who criticize 90 Day Fiancé while also bringing up the subject of cultural diversity as a result of their critical thoughts; and second, those who do so without bringing up the subject at all because they only view the show as entertainment.